Discovering psychology the science of mind - Cacioppo, John T.; aFreberg, Laura (Boston, Massachusetts Cengage Learning, Inc., 2019)
a"DISCOVERING PSYCHOLOGY: THE SCIENCE OF MIND presents psychology as an integrative science that is relevant for students of all majors. John Cacioppo and Laura Freberg use a familiar chapter structure while highlighting connections within psychology as well as between psychology and other disciplines. As they consistently illustrate the benefit of using multiple perspectives within psychology, the authors discuss exciting new research findings likely to expand students' understanding of the field. Psychology is evolving -- and DISCOVERING PSYCHOLOGY, 3rd Edition offers an opportunity to foster a cohesive understanding of the subject as a multidisciplinary, highly interconnected hub science. Also available: the MindTap digital resource"--Provided by publisher.
The science of mind: the discipline of psychology -- The measure of mind: methods of psychology -- The evolving mind: nature and nurture intertwined -- The biological mind: the physical basis of behavior -- The perceiving mind: sensation and perception -- The aware mind: elements of consciousness -- The feeling mind: emotion and motivation -- The adaptive mind: learning -- The knowing mind: memory -- The thinking mind: thinking, language, and intelligence -- The developing mind: lifespan development -- The individual mind: personality and the self -- The connected mind: social psychology -- The troubled mind: psychological disorders -- Healing the troubled mind: therapy -- The healthy mind: stress and coping, health psychology, and positive psychology.
Includes bibliographical references and indexes.
Keywords: Psychology; Psychology -- Textbooks